Pembentukan Citra Politik di Media Sosial Twitter - Rahayu Ramadani; Mifda Hilmiyah (KOMUNIDA : Media Komunikasi dan Dakwah, 2019)
Social media is a form of online mass media where users can easily interact by creating information through blogs, wikis, and other virtual worlds.This research uses the theory of self existence and the theory of the spiral ofsilence. One of the most popular social media in the community is Twitter. Twitteris a social media networking service that gives access to the use of sending,reading and replying to text, image and video based messages with a text limit ofup to 280 characters. Twitter is one of the social media that political leaders useto interact with their supporters and attract public empathy. In its agenda,political figures will more often update Twitter as they approach elections orwhen major issues occur. Social media has a close relationship with politicsbecause social media, especially Twitter, has channels that are close to thecommunity so that people can easily get news directly from political figures.